Uptake and Presentation of Antigen by B Cells - Brooks, Katharine E (University of Edinburgh. College of Science and Engineering. School of Biological Sciences, 2004)
B cells internalize antigen in a specific manner through the B cell receptor (BCR). The antigen is processed into peptides that are loaded on to MHC class II molecules and presented to CD4+ T cells. I have investigated factors that affect how the antigen is taken up, processed and presented.
One way that B cells can obtain antigen is by extracting antigen that is tethered on cells in the form of immune complexes. Follicular dendritic cells (FDCs) are thought to be a type of cell that can provide antigen in this way. B cell acquisition of intact antigen from FDCs is thought to be important during the maturation of an immune response. As previous studies are relative limited due to the technical difficulties of obtaining FDCs, the molecular mechanisms involved in this antigen transfer are still unclear. I have therefore attempted to develop an in vitro system for assessing antigen transfer from FDCs isolated from murine spleen to B cells, with the aim of investigating the molecular requirements for transfer of antigen from FDCs to B cells. In particular, I have studied the role of the BCR on B cells and complement receptors 1 and 2 (CR/2) on FDCs in uptake of antigen by B cells from FDCs.
I have also used soluable antigen to investigate the role of affinity in uptake and presentation of antigen by B cells. I have used a panel of recombinant antigens, together with B cell transfectants expressing antigen-specific BCRs, to study BCR-antigen interactions of varying affinities. T cell hybridomas recognising different epitopes of the antigen allowed me to determine the efficiency of antigen presentation. A high affinity interaction between the BCR and its antigen generally anables more effective presentation than a low affinity one. I have found, however, that the effect of BCR-antigen affinity varies according to the T cell epitopestudied. Under certain circumstances presentatiion may be better when the affinity of the BCR for the antigen is reduced.